The Oxford handbook of Asian business systems - Witt, Michael A. ([Oxford handbooks], 2014)
"The Oxford Handbook of Asian Business Systems aims to address this imbalance by exploring the shape and consequences of institutional variations across the political economies of different societies within Asia. Drawing on the deep knowledge of 31 leading experts, this book presents an empirical, comparative institutional analysis of 13 major Asian business systems between India and Japan. To aid comparison, each country chapter follows the same consistent outline. Complementing the country chapters are eleven contributions examining major themes across the region in comparative perspective and linking the empirical picture to existing theory on these themes. A further three chapters provide perspectives on the influence of history and institutional change. The concluding chapters spell out the implications of all these chapters for scholars in the field and for business practitioners in Asia"--Publisher's website.